IEEE 802.15.4 ZigBee-Based Wireless Sensor Network in MedicalApplication - Jassim, Sabbar; Nourildean, Shayma (Iraqi Journal of Science, 2024)
As a new and promising technology, wireless sensor networks (WSN) plays anessential part in a large number of modern applications. Wireless Sensor Networkscomprised of small, simple, and inexpensive wireless devices – the so-called sensornodes. ZigBee technology provides the framework required to support wirelessnetworks and fills the gap between the IEEE 802.11 WiFi and IEEE 802.15Bluetooth standards in terms of transmission range and data rates. Generally ZigBeeclassified as a low-rate wireless personal area network (LR-WPAN) technology.This paper concerns with the use of WSN in one of many applications which it ispatient monitoring. It performs patient monitoring system using ZigBee WSN. Themodeled system consists of number of wards, each ward had number of sensors foreach patient. Each sensor node represented with ZigBee end device that transmit thetraffic to the master node which it is ZigBee coordinator. Then, The information canbe accessed by the doctor by connecting the system through Ethernet LAN to theserver. This simulation study was done using OPNET modeler V14.5. This paperstudy the performance of the modeled system in terms of delay, throughput, trafficreceived and other parameters that could be taken to study the performance of themodeled system if the number of patients was increased, the effect of increasingmaster nodes and the existence of router. The results showed that single coordinator(master node) system cause more delay, throughput than multiple coordinatorssystem and the existence of router cause additional delay to the system. ZigBeebased WSN for patient monitoring application resulted in online treatment, historyas a database to lead the doctor in order to give proper instructions to the patient.